DEVELOPMENTAL MORPHO-ANATOMY AND GERMINATION OF THE SEEDS OF Pterocarpus indicus f. echinatus Willd. VARIANTS - Kate Capiltan; Lerma Maldia; Marilyn Quimado; Crusty Tinio; Marilyn Combalicer (BIOTROPIA, 2022)
Previous studies on the embryo structure of legumes species had resulted in the division of the Fabaceae family into two great subfamilies based on embryo axis curvature. Research on seed morphology and anatomy adds to the knowledge of taxonomy, evolution and ecology. This study determined the seed developmental anatomy, pod and seed morphology as well as germination characteristics of the observed variants (T1 - small prickles; T2 - medium prickles; T3 - long prickles) of Pterocarpus indicus Willd. f. echinatus locally known as prickly narra in the Mount Makiling Forest Reserve (MMFR). Based on the anatomy of the root (radicle) and shoot apex, the formation of the leaf primordium in T2 seeds after radicle protrusion was more progressive. It was observed that the germination rate and the percentage were the highest in T2, where the apical dome was welldeveloped. The germination, pod and seed morphological characters as well as seed anatomical characters were proven to be systematically informative by showing significant differences among the variants.